Computational Method of Structural Reliability Based on Integration Algorithms - Chen, Chong; Wan, Yi (Sensors & transducers, 2013)
It is very difficult to built reliability design model of structural parts working in a complex and uncertain environment because of their dynamic time-dependent characteristic, an intelligent method of reliability analysis based on integration algorithm is presented in this article, RBFNN and finite element analysis combined with Monte Carlo numerical simulation is integrated to improve simulation computing precision. And this method is applied to reliability analysis of OCS suspension system, mathematic model of reliability calculation on OCS system based on integration algorithm is built, and reliability of OCS suspension system are calculated by the method, and the influence of outside parameter on the whole system is analyzed by the model. OCS suspension system are critical force-bearing parts of OCS system in the high-speed electrified railway, and fault rate is very high, their reliability analysis is important research subject in railway system, the integration algorithm provides feasible new method for the reliability analysis, and design of OCS system and the other Structural system.